2021
DOI: 10.1111/jcpp.13373
|View full text |Cite
|
Sign up to set email alerts
|

Developmental differences in neural connectivity for semantic processing in youths with autism

Abstract: Background: Youths with autism spectrum disorder (ASD) rely more on lower-level visual processing as revealed by greater occipital activation, yet less effectively engage higher-level processing of modality-independent semantic knowledge as indicated by reduced frontal activation, compared to typically developing (TD) youths. However, little is known about age-dependent differences in neural connectivity during semantic processing in youths with ASD as compared to TD youths. Methods: Four groups were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…One of the most interesting features of those with ASD is the ‘unevenness‘ of cognitive abilities. It is a view held by many authors that an effective way to explain the diverse behavioural effects noted in ASD and many other neurobehavioural disorders is by understanding that a significant contribution to ASD is a functional disconnection between areas of the brain30–36 not unlike what is seen in sleep or in minimally conscious states 3 23. Functional asymmetry within widespread cortical networks could result in decreased temporal coherence in certain networks and enhanced temporal coherence in other functional networks.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most interesting features of those with ASD is the ‘unevenness‘ of cognitive abilities. It is a view held by many authors that an effective way to explain the diverse behavioural effects noted in ASD and many other neurobehavioural disorders is by understanding that a significant contribution to ASD is a functional disconnection between areas of the brain30–36 not unlike what is seen in sleep or in minimally conscious states 3 23. Functional asymmetry within widespread cortical networks could result in decreased temporal coherence in certain networks and enhanced temporal coherence in other functional networks.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Japan using fNIRS and a fragrance pulse injection system found that ASD participants with lower odor sensitivity presented reduced activity of the right dorsolateral prefrontal cortex in response to odor stimuli compared to a TD control group [50]. Several studies have also demonstrated that ASD has atypical features of FA and FC when performing language judgment, facial difference recognition, and memory tasks [51][52][53]. Neuroscience research on early identification of ASD or people at high risk for ASD has been emphasized [54,55].…”
Section: Researchmentioning
confidence: 99%
“…As most imaging studies of semantic processing in learning Chinese focus on short-term influences (review in Chung et al, 2019 ), the present study chooses to examine long-term effects on the ventral pathway (i.e., longer than 5years). The chosen learning length of 5years is based on previous imaging studies of semantic development in Chinese using cross-sectional ( Lee et al, 2015 ; Chen et al, 2016 ; Fan et al, 2020 ) and longitudinal approaches ( Lee et al, 2016 ; Chou et al, 2019 ; Fan et al, 2021 ). The long-term learning places substantial impacts on the ventral pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a developmental increase in brain activation has been found in the left IFG and middle/superior temporal gyrus ( Wong et al, 2019 ). In addition, dynamic interaction between brain regions, such as functional connectivity, shows developmental increases on the ventral pathway during semantic judgments ( Fan et al, 2021 ). Taken from developmental implications, it is thus important to examine long-term learning effects on the ventral pathway with semantic processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation